Detection of electrochemiluminescence from floating metal platelets in suspension - Juskova, Petra; Neuzil, Pavel; Manz, Andreas; Foret, Frantisek (Royal Society of Chemistry, 2013)
We present a generation of electrochemiluminescence (ECL) signal, based on square shaped gold electrodes with a size of 50 mm positioned inside a fused silica capillary. The ECL was generated using electric pulses with duration in the range from 100 ms to 5 s and an electrical field strength from 300 V cm(-1) to 500 V cm(-1). We have demonstrated that the electrochemical reaction with detectable optical output can be produced using freely moving and thus disposable electrodes.
Keywords: ELECTROGENERATED CHEMILUMINESCENCE; RUTHENIUM(II); SYSTEM; FABRICATION; SHELLS; SENSOR